Going there [large type] - Couric, Katie, 1957- (Little, Brown and Company, 2021)
In this memoir, the iconic media star discusses her professional and personal life, including losing her husband at a young age, her historic turn as anchor of the CBS Evening News, and experiences dealing with gender inequality.